Investigation of Quantitative Evaluation Method and Engineering Application of Shallow Buried Tunnel Face Stability - Guan-Nan Zhou; Teng-Tian Yang; Ze Sun; Heng Li; Yun Cheng; Zhan-Ping Song; Jing-Jing Han (Applied Sciences, 2022)
The stability of a tunnel face and the rationality of its supporting structures are the guarantees for safe tunnel construction. This paper established a quantitative analysis model of tunnel face stability, obtained the calculation formula of the tunnel face stability coefficient based on the silo theory of surrounding rock, and then realized the quantitative description of stability of the tunnel face under the condition of a pipe roofing support, bolting support, grouting support and reserved core soil. Finally, a tunnel face stability discrimination and support optimization system was developed, its supporting effects were quantitatively evaluated, and the support measures were optimized based on a buried tunnel of Chongqing rail transit passing through the suburban expressway. The results show that the grouting support increased the stability coefficient by 103~412%, and its supporting effect is the most significant. The reinforcement with reserved core soil has the lowest cost. The tunnel face stability discrimination and support optimization system carries out a rapid judgment of tunnel face stability, and then provides a quantitative evaluation method for the assessment of the tunnel face. On-site monitoring indicates that the cumulative displacement gradually increased with monitoring time; the farther from the tunnel surface, the smaller the cumulative displacement. The cumulative displacement reached 34.50 mm before the optimization of the reinforcement scheme. The optimization scheme of pipe roofing support + reserved core soil + grouting support led to the gradual convergence of cumulative displacement. The final surface settlement displacement was reduced to 15.50 mm, which was about 44.93% of that before the optimization of reinforcement scheme, ensuring the safe construction of the buried tunnel. This research has a certain theoretical significance for the quantitative evaluation and analysis of the tunnel face stability of shallow buried tunnels.